An Autocatalytic Platform Combining a Nonlinear Hybridization Chain Reaction and DNAzyme to Detect microRNA - Hongbo Zhang; Xiuen Cao; Qubo Zhu (Bio-Protocol)
MicroRNAs (miRNAs) are small, non-coding RNAs that play pivotal roles in gene regulation; they are increasingly recognized as vital biomarkers for various diseases, notably cancer. Conventional methods for miRNA detection, such as quantitative PCR and microarray analysis, often entail intricate sample preparation and lack the requisite sensitivity to detect low-abundance miRNAs like miRNA-21. This protocol presents an innovative approach that combines branched hybridization chain reaction (bHCR) with DNAzyme technology for the precise detection of miRNA-21. The bHCR amplifies the target signal through a branched structure, while the DNAzyme boosts detection sensitivity through catalytic cleavage, enabling swift and specific identification of miRNA-21. This dual amplification strategy offers a highly sensitive, specific, and rapid alternative to traditional techniques, making it particularly well-suited for early-stage disease diagnosis.